2011
DOI: 10.1186/1479-5876-9-23
|View full text |Cite
|
Sign up to set email alerts
|

Time-course of sFlt-1 and VEGF-A release in neutropenic patients with sepsis and septic shock: a prospective study

Abstract: BackgroundSeptic shock is the most feared complication of chemotherapy-induced febrile neutropenia. So far, there are no robust biomarkers that can stratify patients to the risk of sepsis complications. The VEGF-A axis is involved in the control of microvascular permeability and has been involved in the pathogenesis of conditions associated with endothelial barrier disruption such as sepsis. sFlt-1 is a soluble variant of the VEGF-A receptor VEGFR-1 that acts as a decoy receptor down-regulating the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 31 publications
2
23
2
1
Order By: Relevance
“…In fact, we were not able to confirm previous reports of VEGF-A or sFlt-1 as informative biomarkers of septic shock development in patients with FN [23,32]. We speculate that these discrepancies are associated with differences in the time-point of sample collection, and with the potential influence of severe neutropenia and thrombocytopenia in the variation of VEGF-A, as neutrophils and platelets are major sources of these mediator [33].…”
Section: Discussioncontrasting
confidence: 88%
“…In fact, we were not able to confirm previous reports of VEGF-A or sFlt-1 as informative biomarkers of septic shock development in patients with FN [23,32]. We speculate that these discrepancies are associated with differences in the time-point of sample collection, and with the potential influence of severe neutropenia and thrombocytopenia in the variation of VEGF-A, as neutrophils and platelets are major sources of these mediator [33].…”
Section: Discussioncontrasting
confidence: 88%
“…Increased concentrations of sFlt-1 have been shown in sepsis and have been positively associated with more severe sepsis [16,28,29,30,31]. In 2010, Shapiro et al [16] reported a strong association between sFlt-1 plasma concentrations and the severity of sepsis, as well as the development of organ dysfunction in sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF and VEGFR1 on the cell surface are up-regulated after endothelial injury, promoting reendothelialization by enhancing vascular remodeling [28]. These results suggest that higher sVEGFR1 levels may hamper VEGF signaling in the process of endothelial repair, thereby leading to disease progression and organ dysfunction [5,29]. Furthermore, high circulating sVRGFR1 levels correlate with morbidity and mortality, and are a potent marker of disease severity in septic or critically ill patients [5,26].…”
Section: Discussionmentioning
confidence: 99%